The Role of Technology in Enhancing Global Education Access and Equity - Håkan Forsberg; Anders Holmström; Maja Persson (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
This paper explores how technology can bridge the gap in global education, providing greater access and equity to underserved populations. By analyzing various digital learning platforms and initiatives, the study examines their impact on education in remote areas and developing countries. The research highlights how mobile learning, online courses, and virtual classrooms are revolutionizing education, making learning more accessible and inclusive for students globally.